Analysis of the Role of Augmented Reality in Bringing Works of Art to Digital Spaces - Yuniana Cahyaningrum; Cahya Surya Harsakya; Septianingrum, Salsabila Putri (Apik Cahaya Ilmu, 2024)
Augmented Reality (AR) has become increasingly popular in the art world as a medium for bringing traditional works of art into the digital space. This research aims to analyze the role played by AR technology in the process of transforming works of art from the physical environment into the digital domain. This approach pays attention to the technical aspects, aesthetics and cultural impact of applying AR in digital art exhibitions. This research method involves literature analysis, case studies of various art exhibitions that use AR, and interviews with artists, curators, and exhibition visitors. Qualitative data was analyzed thematically to identify emerging patterns and trends in the use of AR in artistic contexts. The research results show that AR has great potential to enrich the visitor experience in digital art exhibitions by providing interactive and contextual layers that cannot be accessed through conventional mediums. Additionally, AR can also act as a tool to convey additional narratives, broaden the interpretation of works of art, and increase visitor participation in the creative process. The research also identified several technical and conceptual challenges associated with the use of AR in art, including issues of technological sustainability, accessibility, and artwork integrity. Nonetheless, overall, this research highlights the great potential of AR in bringing works of art into digital spaces and provides valuable insights for the future development of digital art exhibitions.